Pengaruh Penerimaan Pajak Kendaraan Bermotor, Denda Pajak, dan Bea Balik Nama Kendaraan Bermotor terhadap Pendapatan Asli Daerah Kabupaten Deli Serdang - Jayanti, Sri; Wirananda, Henny Andriyani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The purpose of this study was to determine the effect of Motor Vehicle Tax, Tax Fines and Motor Vehicle Transfer Fees on the Original Regional Income of Deli Serdang Regency, and to analyze the effect of Motor Vehicle Tax, Tax Fines and Motor Vehicle Transfer Fees together on the Original Regional Income of Deli Serdang Regency in 2019-2022 in monthly. The data collection technique used in this study was a documentation study. This study used multiple linear regression analysis methods. The results of the study showed that Motor Vehicle Tax had an effect on the Original Regional Income of Deli Serdang Regency, Tax Fines had a significant effect on the original regional income of Deli Serdang Regency and Motor Vehicle Transfer Fees had no effect on the Original Regional Income of Deli Serdang Regency. Motor Vehicle Tax, Tax Fines and Motor Vehicle Transfer Fees together had an effect on the Original Regional Income of Deli Serdang Regency. Motor Vehicle Tax, Tax Fines and Motor Vehicle Transfer Fees have a strong relationship to Regional Original Income, which is 0.814, or Motor Vehicle Tax, Tax Fines and Motor Vehicle Transfer Fees to Regional Original Income of Deli Serdang Regency, which is 81.4% while the remaining 18.6% is influenced by other factors not included in this study.